Antenatal Care Services Utilization in Yobe State, Nigeria: Examining Predictors and Barriers - Abubakar Sadiq Umar, MBBS, MPH, MHPM, FWACP; Samuel Bitrus Bawa, MBBS, MPH, FWACP (Global Health and Education Projects, Inc., 2015)
Objective: In Nigeria, wide disparities exist between the different parts of the country, with the states in the North East zone having poor health resources. The objective of this study is to assess whether women's biological, sociocultural, and economic characteristics are associated with utilization of ante natal care services as measured by number of antenatal care (ANC) visits in Yobe State. Methods: This is a secondary data analysis of the 2008 Nigeria Demographic and Health Survey with records from 33,385 women between 15-49 years who had given birth between January 2003 and December 2008 in Yobe State. Bivariate Pearson's Chi square test and two stages of Multivariate regression analysis were conducted. Results: Women with at least primary level education (adjusted OR (AOR) = 2.40; CI 1.24 - 4.67), belonging to professional employment category (AOR = 12.07; CI 0.19 - 75.74) and those who had access to skilled health workers (AOR = 5.13; CI 2.50 - 10.52) are more likely to make the required number of ANC visits compared to those who are illiterates, unemployed and had no access to skilled health workers. Conclusion and Global Health Implications: This study demonstrated that educational level, family wealth income, and availability of skilled health worker were consistently associated with the number of ANC visits even after controlling for covariates. These three covariates are in tandem with the Millenium Development Goals (MDG) 1 - eradication of extreme poverty and hunger; MDG 2 - universal basic education; MDG 3 - gender equality; and MDG 4 - maternal mortality. There is the need for inter-sectoral holistic intervention approach.